Mental health and its correlates among children and adolescents during COVID-19 school closure: The importance of parent-child discussion - Tang, Suqin; Xiang, Mi; Cheung, Teris; Xiang, Yu-Tao (Journal of affective disorders, 2021)
•A representative sample of 4342 primary and secondary school students were investigated.•The three most prevalent symptoms were: anxiety (24.9%), depression (19.7%), and stress (15.2%).•Students were generally satisfied with life and 21.4% became more satisfied with life.•Perceived benefit and parent-child discussion were protective factors of mental health.•Parent-child discussion was related to less symptoms even in students perceived no benefit from home quarantine. School closures due to the COVID-19 outbreak have affected 87% of the world's students physically, socially, and psychologically, yet rigorous investigation into their mental health during this period is still lacking. A cross-sectional online survey of 4-342 primary and secondary school students from Shanghai, China was conducted during March 13–23, 2020. Besides demographic information, psychological distress (including depression, anxiety, and stress), life satisfaction, perceived impact of home quarantine, and parent-child discussions on COVID-19 were assessed. The three most prevalent symptoms were: anxiety (24.9%), depression (19.7%), and stress (15.2%). Participants were generally satisfied with life and 21.4% became more satisfied with life during school closures. Senior grades were positively correlated with psychopathological symptoms and negatively associated with life satisfaction, whereas the perceived benefit from home quarantine and parent-child discussions on COVID-19 were negatively correlated with psychopathological symptoms and positively correlated with life satisfaction. Among participants who perceived no benefit from home quarantine, those who had discussions with their parents about COVID-19 experienced less depression, anxiety, and stress. Limitations included the inability to infer the casual relationship, no parental report for mental health of children aged 6 to 9, and the inadequate measurement of parent-child discussion. Mental health problems and resilience co-existed in children and adolescents during the COVID-19 outbreak. Given the important role of parent-child discussions, open communication between parents and children about the pandemic should be encouraged to help children and adolescents cope with mental health problems in public health crisis.